2002
DOI: 10.1142/s0217979202015030
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASONIC PROPERTIES AND ELECTRON-PHONON COUPLING CONSTANT IN TlSr2(M1 - xYx)Cu2O7 (M = Ca, Sr) SUPERCONDUCTOR

Abstract: Ultrasonic properties of bulk TlSr 2 (M 1−x Yx)Cu 2 O 7 (M = Ca, Sr) high temperature superconductors have been measured between 80 and 280 K. Sound velocity measurements show that all samples exhibit an overall stiffening trend with decreasing temperature. The longitudinal sound velocity shows a pronounced slope change and attenuation peak around 200 K. The results were explained in terms of phase transition and distortion of Tl and O atoms associated with local oxygen ordering. The calculated acoustic Debye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…[8] showed similar step-like elastic anomalies above 230 K. In the present work, the existence of the step-like elastic anomaly was suggested to be due to some form of oxygen ordering taking place in TlÀO planes. A similar explanation was reported for other Tl1212 samples such as TlSr 2 (Ca 1¡x Pr x )Cu 2 O 7¡d , [13] TlSr(Sr 1¡x Y x )Cu 2 O 7 [12] and TlSr 2 (M 1¡x Y x )Cu 2 O 7 (M D Ca, Sr), [11] where it was suggested that the step-like elastic anomaly reflects the possibility of structural distortion of TlÀO planes related to the existence of short-range oxygen ordering in TlÀO (3) superstructures. In these samples, differences in oxygen content may not be the main factor affecting the results as the same preparation condition was used.…”
Section: Discussionsupporting
confidence: 84%
“…[8] showed similar step-like elastic anomalies above 230 K. In the present work, the existence of the step-like elastic anomaly was suggested to be due to some form of oxygen ordering taking place in TlÀO planes. A similar explanation was reported for other Tl1212 samples such as TlSr 2 (Ca 1¡x Pr x )Cu 2 O 7¡d , [13] TlSr(Sr 1¡x Y x )Cu 2 O 7 [12] and TlSr 2 (M 1¡x Y x )Cu 2 O 7 (M D Ca, Sr), [11] where it was suggested that the step-like elastic anomaly reflects the possibility of structural distortion of TlÀO planes related to the existence of short-range oxygen ordering in TlÀO (3) superstructures. In these samples, differences in oxygen content may not be the main factor affecting the results as the same preparation condition was used.…”
Section: Discussionsupporting
confidence: 84%
“…The weak anomaly which was characterized by slowing down of hardening rate, but which does not seem to amount to a softening, is a signal of nucleation of a phase transition where oxygen ordering begins to take place. Previous reports on step-like elastic anomalies observed in other Tl-based samples such as TlSr 2 (Ca 1 À x Pr x )Cu 2 O 7 À δ [6], TlSr(Sr 1 À x Y x )Cu 2 O 7 [23] and TlSr 2 (M 1 À x Y x )Cu 2 O 7 (M ¼Ca, Sr) [22] reflects the possibility of structural distortion of Tl-O planes and is attributed to existence of short-range ordering in the Tl-O(3) superstructures. On the other hand, the Cd substitution shows increase in slope change of the step-like anomaly from 0.0091 GPa/K to 0.0791 GPa/K (x ¼0.3) before decreasing to 0.0569 GPa/K (x ¼0.4) (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, Tl1212 is iso-structural to the YBa 2 Cu 3 O 7 À δ system [21] and temperature dependence of sound velocity in samples showed strong influence of the substitutions on elastic behavior. For instance, for [22], longitudinal velocity measurements revealed step-like elastic anomaly indicating pronounced lattice hardening around 230 K. The existence of elastic anomaly in the sample has been proposed to correspond to some kind of oxygen ordering taking place in Tl-O planes [6,22,23]. However, compared to RE123 reports on ultrasonic measurements on Tl-based were quite limited.…”
Section: Introductionmentioning
confidence: 96%
“…The last model account well for the magnitudes of T c and the oxygen isotope exponent of the superconductor cuprates. Calculations with BCS theory and van Hove scenario have also been done with d-wave pairing [12]. The validity of d-wave BCS formalism in high-T c superconductor cuprates has been supported by measurements of transport properties and ARPES [13].…”
Section: Introductionmentioning
confidence: 99%